Development plan; educational institution; social construction of reality; resignification. - J. O. Sánchez; A. L. Ortiz; I. M. Sánchez (Universidad del Magdalena, 2013)
This article is part of the final results and the discursive developments achieved in the framework of the project Expedition Celedon in 2011 in its academic component of formulation of the ten-year Development Plan. (PDI). This project is based on research processes that have generated relevant scientific knowledge in academia and relevant social; from the systematization of the process and the results of the exercise of community involvement that led to the structuring of the PDI. Underlying the nature of lecturers and researchers on the basis of the conception of the nature of the educational institution; assumed a perspective emerging as social fabric, as communications network and senses, such as merger of formal and social components such as complex systemic unity, as avocado uncertainty... as an organization built scenario and that is socially constructed.